Dams and Reservoirs : Planning and Engineering - Iqtidar H. Siddiqui (Karachi Oxford University Press, 2009)
This book has been written specially for undergraduate and postgraduate students and professional engineers involved in the planning and design of small and large dam projects with emphasis on planning, investigation, design, construction and their maintenance.
Include Maps, Illustrations, Graphs, Tables, Bibliography and Index.
Keywords: Reservoirs--Design and construction -- Dams--Design and construction -- Water--Distribution--Management -- Pakistan